TMEM182 interacts with integrin beta 1 and regulates myoblast differentiation and muscle regeneration. Issue 6 (23rd August 2021) - Luo, Wen; Lin, Zetong; Chen, Jiahui; Chen, Genghua; Zhang, Siyu; Liu, Manqing; Li, Hongmei; He, Danlin; Liang, Shaodong; Luo, Qingbin; Zhang, Dexiang; Nie, Qinghua; et al.
Abstract: Background: Transmembrane proteins are vital for intercellular signalling and play important roles in the control of cell fate. However, their physiological functions and mechanisms of action in myogenesis and muscle disorders remain largely unexplored. It has been found that transmembrane protein 182 ( TMEM182 ) is dramatically up‐regulated during myogenesis, but its detailed functions remain unclear. This study aimed to analyse the function of TMEM182 during myogenesis and muscle regeneration. Methods: RNA sequencing, quantitative real‐time polymerase chain reaction, and immunofluorescence approaches were used to analyse TMEM182 expression during myoblast differentiation. A dual‐luciferase reporter assay was used to identify the promoter region of the TMEM182 gene, and a chromatin immunoprecipitation assay was used to investigate the regulation TMEM182 transcription by MyoD. We used chickens and TMEM182 ‐knockout mice as in vivo models to examine the function of TMEM182 in muscle growth and muscle regeneration. Chickens and mouse primary myoblasts were used to extend the findings to in vitro effects on myoblast differentiation and fusion. Co‐immunoprecipitation and mass spectrometry were used to identify the interaction between TMEM182 and integrin beta 1 (ITGB1). The molecular mechanism by which TMEM182 regulates myogenesis and muscle regeneration was examined by Transwell migration, cell wound healing, adhesion, glutathione‐S‐transferse pull down, protein purification, and RNA immunoprecipitation assays. Results: TMEM182 was specifically expressed in skeletal muscle and adipose tissue and was regulated at the transcriptional level by the myogenic regulatory factor MyoD1. Functionally, TMEM182 inhibited myoblast differentiation and fusion. The in vivo studies indicated that TMEM182 induced muscle fibre atrophy and delayed muscle regeneration. TMEM182 knockout in mice led to significant increases in body weight, muscle mass, muscle fibre number, and muscle fibre diameter. Skeletal muscle regeneration was accelerated in TMEM182 ‐knockout mice. Furthermore, we revealed that the inhibitory roles of TMEM182 in skeletal muscle depend on ITGB1, an essential membrane receptor involved in cell adhesion and muscle formation. TMEM182 directly interacted with ITGB1, and this interaction required an extracellular hybrid domain of ITGB1 (aa 387–470) and a conserved region (aa 52–62) within the large extracellular loop of TMEM182 . Mechanistically, TMEM182 modulated ITGB1 activation by coordinating the association between ITGB1 and laminin and regulating the intracellular signalling of ITGB1. Myogenic deletion of TMEM182 increased the binding activity of ITGB1 to laminin and induced the activation of the FAK‐ERK and FAK‐Akt signalling axes during myogenesis. Conclusions: Our data reveal that TMEM182 is a novel negative regulator of myogenic differentiation and muscle regeneration.